The Relationship Between Fiber Intake And Body Mass Index (Bmi) With Total Cholesterol Levels In Students Of Biology Department University Of Lampung - Claudia Clara; Dian Isti angraini; Sofyan Musyabiq; Dyah Wulan Sumekar RW (CV. Jasa Sukses Abadi, 2020)
Total cholesterol levels in body play an important role in the process of degenerative diseases. Total cholesterol levels are affected by age, intake of fiber, fat, carbohydrates and protein, physical activity and body mass index. This study aimed to determine the relationship between fiber intake and body mass index (BMI) with total cholesterol levels in students of Biology Department University of Lampung. This study used analytic-correlative research method with cross sectional approach. Sampling was taken by disproportionate stratified random sampling and obtained 43 respondents, aged 18-22 years. This research was conducted on November 2017 in Biology Department of Matematics and Sains, Faculty University of Lampung. The results showed that the average intake of fiber was 4,20 grams/day; the average of body mass index was 21,719; the average of total cholesterol levels was 180,4 mg/dl. Results showed significant relationship between fiber intake and total cholesterol levels with medium correlation (r=-0,470, p = 0,001) and significant relationship between body mass index and total cholesterol levels with medium correlation (r=0,510 p =0,000). There was relationship between fiber intake and body mass index (BMI) with total cholesterol levels in students of Biology Department University of Lampung.